An examination of the role of Big Five personality traits on employee creativity in Sudanese public universities: a gender-based approach - Amoozegar, Azadeh; Elsiddig, Basma Mohamed Hassan; Falahat, Mohammad; Ikram, Maryam; Ismaeil, Ayman Abdel Rahman Mohamed; Krishnasamy, Hariharan N. (Frontiers in Psychology, 2025)
IntroductionSudanese higher education institutions must recognize the influence of Big Five personality traits on employee creativity to foster a workforce that is both innovative and adaptable. These traits play a key role in shaping how employees approach their work and generate new ideas. While studies have explored the link between each of the Big Five personality traits and creativity, the findings have been varied.MethodsThis research employed a cross-sectional correlational approach to examine how the Big Five personality traits influence employee creativity in public universities in Sudan. Participants in the study were randomly selected from five public universities in South Sudan. Data analysis was carried out using SmartPLS 4.ResultsThe findings of this research showed that Openness, Agreeableness, and Consciousness significantly influenced creativity, whereas Extraversion and Neuroticism did not. Additionally, the relationship between the Big Five personality traits and creativity was not moderated by gender.DiscussionIdentifying employee personality types and how they influence creativity is crucial for university management when hiring academic staff, especially in developing countries, since it can help them select individuals more likely to excel at research, teaching, and innovation. This knowledge can also inform employment policy to foster an environment conducive to creativity and growth.